Assessment of Microwave Effect on Polymerization Conducted under ARGET ATRP Conditions. Issue 1 (12th October 2017) - Xie, Zhi‐Kang; Guo, Jun‐Kang; Luo, Zheng‐Hong
Abstract: A comprehensive kinetic model based on the method of moments is developed for understanding the kinetics of activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP) under microwave irradiation. Both the experimental data and the simulation results show that the polymerization under microwave irradiation is much faster than the thermal polymerization. Simulation results indicate that the acceleration of polymerization can be attributed to the increase of propagation rate coefficient and the radical generation by microwave irradiation. Kinetic behaviors, such as the effect of catalyst concentration and initial initiator, are investigated in detail. Results show that the catalyst concentration has negligible influence on polymerization rate while the initiator concentration can affect both the molecular weight and the reaction rate. In conclusion, this work thoroughly investigates the kinetic mechanism of ARGET ATRP under microwave irradiation, providing both theoretic and experimental supports to improve the product property of polymer materials. Abstract : A comprehensive kinetic model for the activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP) under microwave irradiation is developed to understand the kinetic mechanism. The key polymerization kinetic behaviors under microwave irradiation are obtained in this work using the simulation way. Therefore, this work deeply investigates the kinetic mechanism of ARGET ATRP under microwave irradiation.